Rancang Bangun Aplikasi Mobile Struktur Data Graf Berbasis Google Maps - Devara Fikry Akmal; Aryo Pinandito; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Google Maps is a popular navigation system on mobile devices with over 1 billion user downloads on Play Store. One of the key features in Google Maps is direction, that can provide travel route. However, in determining travel routes, Google Maps makes use of the listed roadmap causing the available routes not necessarily to take into account the applicable rules and provide the shortest route of a place, including within the Brawijaya University. Therefore, it is necessary that the Aplikasi Mobile Struktur Data Graf can create a special travel graph data structure for the Brawijaya University environment so that it can be implemented to determine the closest route that follow the rules in Brawijaya University. This app serves to insert Point on the map and build a graph that can function as a travel route. Application developed by using Software Development Lifecycle Incremental Model, where each development is divided into increment to simplify the application development. Application development is designed using an object-oriented approach that is represented using UML (Unified Modeling Languange). This application has been successfully completed through 2 increment, increment 1 and increment 2. In increment 1, the application has fulfilled the functionality to create the graph data structure in Brawijaya University, while in increment 2, the application has fulfilled the functionality to implement the graph data strutur with the algorithm Djikstra to determine the closest route. Application in each increment has been tested using White Box Testing method using Base Path Testing technique for unit testing and Black Box Testing method for validation testing with 100% success.